Looking across diverse food system futures: Implications for climate change and the environment - Zurek, Monika; Hebinck, Aniek; Selomane, Odirilwe (Oxford University Press, 2021)
Agriculture and food systems are in urgent need of transformation. Various foresight reports unpack food systems’ challenges and propose diverse pathways of change towards sustainability. We interrogate the framings and proposed pathways of eleven selected reports from a food system perspective, with a focus on environmental and climate change implications. We synthesize key drivers of food systems and their impact on food system outcomes. We distil trends and strategies identified across the reports and their scenarios and discuss the diversity of ‘sustainability pathways’ and ‘solution spaces’. There is general agreement that resource protection and adaptation balanced with significant greenhouse gas emission reductions are vital to food system transformation. There is less consensus on the choice of change options and how to address potential trade-offs. While new technologies or consumption changes are described, more attention needs to be paid to overcoming blind spots like implications for equity or changes in governance mechanisms.